6-Phenyl-3-(4-pyridyl)-1,2,4-triazolo-[3,4-b][1,3,4]thiadiazole: Synthesis, experimental, theoretical characterization and biological activities - Cansiz, Ahmet; Cetin, Ahmet; Orek, Cahit; Karatepe, Mustafa; Sarac, Kamiran; Kus, Alper; Koparir, Pelin (Pergamon-Elsevier Science Ltd, 2012)
The molecular geometry, vibrational frequencies, and gauge including atomic orbital (CIAO) H-1 and C-13 NMR chemical shift values of the title compound in the ground state have been calculated using the Hartree-Fock (HF) and density functional theory (DFT) methods with 6-31G(d) basis sets, and compared with the experimental data. The calculated results show that the optimized geometries can well reproduce the crystal structural parameters and the theoretical vibrational frequencies, and H-1 and C-13 NMR chemical shift values show good agreement with experimental data. To determine conformational flexibility, molecular energy profile of the title compound was obtained by HF/6-31G(d) and (DFT/B3LYP) calculations with respect to selected degree of torsional freedom, which was varied from -180 degrees to +180 degrees in steps of 10 degrees. The energetic behavior of the title compound in solvent media was examined using the B3LYP method with the 6-31G(d) basis set by applying the Onsager and the polarizable continuum model (PCM). The results obtained with these methods reveal that the PCM method provided more stable structure than Onsager's method. The title compound has been tested in vitro for biological effects. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 6-Phenyl-3-(4-pyridyl)-1,2,4-triazolo-[3,4-b][1,3,4]thiadiazole; DFT; HF; NMR; IR spectra; Biological effects